Stem rust resistance in Aegilops tauschii germplasm - Rouse, Matthew N.; Olson, Eric L.; Gill, Bikram S.; Pumphrey, Michael O.; Jin, Yue (My University, 2011)
Aegilops tauschii Coss., the D genome donor of hexaploid wheat, Triticum aestivum L., has been used extensively for the transfer of agronomically important traits to wheat, including stem rust resistance genes Sr33, Sr45, and Sr46. To identify potentially new stem rust resistance genes in A. tauschii germplasm, we evaluated 456 nonduplicated accessions deposited in the USDA National Small Grains Collection (Aberdeen, ID) and the Wheat Genetic and Genomic Resources Center collection (Kansas State University, Manhattan, KS), with races TTKSK (Ug99), TRTTF, TTTTF, TPMKC, RKQQC, and QTHJC of Puccinia graminis Pers.:Pers. f. sp. tritici Eriks. & E. Henn. Ninety-eight accessions (22%) were identified as resistant to race TTKSK. A broad range of resistant infection types (; to 2+) were found in reaction to race TTKSK. Resistance was significantly associated among most of the races in pairwise comparisons. However, resistance was largely race specific. Only 12 of the accessions resistant to race TTKSK were also resistant to the other five races. Results from this germplasm screening will facilitate further studies on the genetic characterization of accessions with potentially novel sources of resistance to race TTKSK.
Citation: Rouse, M.N., Olson, E.L., Gill, B.S., Pumphrey, M.O., & Jin, Y. (2011). Stem rust resistance in Aegilops tauschii germplasm. Retrieved from http://krex.ksu.edu
Keywords: Wheat; Stem rust resistance; Aegilops tauschii germplasm; Eastern Africa